Effects of Reasoning Ability on Field Goal Shooting Skills of Female Basketball Players - Virendra Kumar Singh; C. D. Agashe (The Society of Aging and Physical Activity (SAPA), 2014)
In the present study, field goal shooting skills of female basketball players were assessed in the background to their reasoning ability. The sample consists of 100 female intercollegiate basketball players (age = 21.05±1.67 yrs.). Shooting skills reasoning ability were assessed by Johnson's "Basketball Field Goal Speed Shooting Test" and Mixed Type Group Test of Intelligence prepared by Mehrotra (1984), respectively. Results reveal that field goal shooting ability of female basketball players exhibiting superior reasoning ability was found to be significantly better as compared to field goal shooting ability of female basketball players with low and average reasoning ability. It was concluded that shooting skills of female basketball players is influenced by their cognitive ability i.e. ability to rationalize problems in proper sequence.